علاقة بعض العوامل باستخدام زراع جمعية دحلة التعاونية - نجم الدين عبدالله اسماعيل; جعفر علي اللوزي (PROSPECTIVE RESEARCHES, 2023)
The purpose of this study is to identify the agricultural information sources which are utilized by farmers in Dijlah cooperative Society and, determine the factors associated with utilization of agric.inf. Sources. Data were collected by a personal interview with the help of a questionnaire. A sample of (128) farmers out of (745) was taken by using the simple random sample technique. Data were analyzed by using simple correlation and step wise multiple regression by the computer. The following factors showed positive significant association with utilization of Agric. inf. Source "Farmer's education, Social participation, and standard of living "while Farmers age, and family size "showed negative significant association. It has been found that "farmer's education age and social participation were the most important factors in predicting the respondents behavior respectively.